2012
DOI: 10.1242/jcs.109041
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensing by Prolyl-4-Hydroxylase PHD2 within the nuclear compartment and the influence of compartimentalisation on HIF-1 signalling

Abstract: SummaryHypoxia-inducible factors (HIFs) regulate more than 200 genes involved in cellular adaptation to reduced oxygen availability. HIFs are heterodimeric transcription factors that consist of one of three HIF-a subunits and a HIF-b subunit. Under normoxic conditions the HIFa subunit is hydroxylated by members of a family of prolyl-4-hydroxylase domain (PHD) proteins, PHD1, PHD2 and PHD3, resulting in recognition by von-Hippel-Lindau protein, ubiquitylation and proteasomal degradation. It has been suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 34 publications
5
57
0
Order By: Relevance
“…Thus, nuclear export of PHD2 depends on the major exportin CRM1. Note that recent studies have not confirmed the NES between Leu-188 and Iso-198 that was predicted from in silico experiments [85]. Instead, immunofluorescence analyses have revealed that the nuclear export of PHD2 depends on an intact motif between aa Gly-6 and Tyr-20 without a classical leucine-rich NES consensus motif.…”
Section: Intracellular Distribution Of the Hif-α Hydroxylasesmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, nuclear export of PHD2 depends on the major exportin CRM1. Note that recent studies have not confirmed the NES between Leu-188 and Iso-198 that was predicted from in silico experiments [85]. Instead, immunofluorescence analyses have revealed that the nuclear export of PHD2 depends on an intact motif between aa Gly-6 and Tyr-20 without a classical leucine-rich NES consensus motif.…”
Section: Intracellular Distribution Of the Hif-α Hydroxylasesmentioning
confidence: 90%
“…Nuclear import of PHD2 does not occur via classical importin α/β receptors. Although the primary sequence of PHD2 exhibits a motif with weak resemblance to a classical NLS between Arg-99 and Lys-115, PHD2 does not bind to importin α isoforms [85]. Moreover, coregulation of nuclear import of PHD2 and HIF-1α by importin α/β receptors was excluded.…”
Section: Intracellular Distribution Of the Hif-α Hydroxylasesmentioning
confidence: 99%
See 1 more Smart Citation
“…PHD is a cellular sensor for low-oxygen. Under normal oxygen partial pressure and in the presence of Fe 2+ and acetone dicarboxylic acid, PHD catalyzes the hydroxylation of key amino acid residues in the HIF-α ODD domain (42,43). This is followed by VHL binding to HIF-α and inducing degradation via the ubiquitin-proteasome pathway (44,45).…”
Section: Regulation Of Hif-3α Expression At the Post-transcriptional mentioning
confidence: 99%
“…Commonly, the disc undergoes degeneration, a condition frequently linked to neck and back pain and requiring pharmacological or surgical intervention. Degenerative disc disease is characterized by elevated levels of proinflammatory cytokines including TNF-␣, IL-1␤, IL-6, and IL-8, as well as down-regulation of expression of the important matrix molecules aggrecan and collagen II (1)(2)(3)(4). TNF-␣ and IL-1␤ stimulate production of NGF, BDNF, and VEGF, molecules associated with nerve ingrowth and pain as well as angiogenesis (5).…”
mentioning
confidence: 99%